Dual-MWCNT Probe Thermal Sensor Assembly and Evaluation Based on Nanorobotic Manipulation inside a Field-Emission-Scanning Electron Microscope. (18th March 2015) - Yang, Zhan; Wang, Pengbo; Shen, Yajing; Chen, Tao; Chen, Liguo; Huang, Qiang; Sun, Lining; Fukuda, Toshio
We report a thermal sensor composed of two multiwalled carbon nano-tubes (MWCNTs) inside a field-emission-scanning electron microscope. The sensor was assembled using a nanorobotic manipulation system, which was used to construct a probe tip in order to detect the local environment of a single cell. An atomic force microscopy (AFM) cantilever was used as a substrate; the cantilever was composed of Si3 N4 and both sides were covered with a gold layer. MWCNTs were individually assembled on both sides of the AFM cantilever by employing nanorobotic manipulation. Another AFM cantilever was subsequently used as an end effector to manipulate the MWCNTs to touch each other. Electron-beam-induced deposition (EBID) was then used to bond the two MWCNTs. The MWCNT probe thermal sensor was evaluated inside a thermostated container in the temperature range from 25°C to 60°C. The experimental results show the positive characteristics of the temperature coefficient of resistance (TCR).